2020
DOI: 10.2147/ijwh.s250832
|View full text |Cite
|
Sign up to set email alerts
|

<p>Individual, Household, and Contextual Factors Influencing the Timing of the First Antenatal Care Attendance in Northwest Ethiopia: A Two-Level Binary Logistic Regression Analysis</p>

Abstract: Background: Early antenatal visit is critical for the health and well-being of mothers and babies. However, various individual, family level, and contextual factors influence the timely initiation of antenatal care. Objective: The aim of this study was to examine individual, household, and communitylevel factors associated with the timing of first ANC visit among mothers who gave birth in the last twelve months before the survey. Methods: A community-based cross-sectional study was conducted in June 2018. A mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
5
7
0
Order By: Relevance
“…Moreover, education is again proven to play a role in a person’s perception of health services quality [ 48 , 49 ]. Several previous studies also found results in line with this research in various countries, including Kenya, Bangladesh, and Ethiopia [ 50 52 ]. Several other lessons also inform that education is a robust positive determinant of boosting performance in the health sector [ 3 , 53 , 54 ].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, education is again proven to play a role in a person’s perception of health services quality [ 48 , 49 ]. Several previous studies also found results in line with this research in various countries, including Kenya, Bangladesh, and Ethiopia [ 50 52 ]. Several other lessons also inform that education is a robust positive determinant of boosting performance in the health sector [ 3 , 53 , 54 ].…”
Section: Discussionsupporting
confidence: 90%
“…This study included determinants of ANC frequency based on evidence from available literature and data [ 3 , 13 , 26 – 28 ]. Nineteen explanatory variables were used: (1) maternal age, (2) wealth index, (3) level of education, (4) place of residence, (5) region, (6) marital status, (7) working status, (8) ANC timing of first contact, (9) sex of household head, (10) household size, (11) woman’s religion, (12) parity, (13) exposure to newspapers, (14) exposure to television (TV), (15) exposure to radio, (16) internet use, (17) having problems with getting permission to seek help, (18) having problems with distance to the nearby health facility and (19) being visited by a fieldworker.…”
Section: Methodsmentioning
confidence: 99%
“…The reduction in maternal and neonatal mortality results from health education, timely disease prevention, screening and treatment [ 3 , 4 ]. Timely ANC access also maximizes the window of opportunity for ANC skilled providers to counsel pregnant women to opt for skilled birth attendance [ 8 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study included determinants of ANC frequency based on evidence from available literature and data [3,11,[19][20][21]. Nineteen explanatory variables were used: (1) maternal age, (2) wealth index, (3) level of education, (4) place of residence, (5) region, (6) marital status, (7) working status, (8) ANC timing of rst contact, (9) sex of household head, (10) household size, (11) woman's religion, (12) parity, (13) exposure to newspapers, (14) exposure to television (TV), (15) exposure to radio, (16) internet use, (17) having problems with getting permission to seek help, (18) having problems with distance to the nearby health facility and ( 19) being visited by a eldworker.…”
Section: Independent Variablesmentioning
confidence: 99%
“…The reduction in maternal and neonatal mortality results from health education, timely disease prevention, screening and treatment [3,4]. Timely ANC access also maximizes the window of opportunity for ANC skilled providers to counsel pregnant women to opt for skilled birth attendance [11].…”
Section: Introductionmentioning
confidence: 99%